1998 - 2018: Analysis of Indonesian and Malaysian People's Palm Oil Plantations - Koko Setiawan; Sri Gunawan; Heri Setyawan; Hartono Hartono (Akademi Komunitas Perkebunan Yogyakarta, 2022)
This paper aims to analyze the oil palm plantations of the people of Indonesia and Malaysia in the last 1998-2018 years to be able to analyze the broadness, production and productivity trends and compare the performance of people's oil palm plantations in both countries. This research was conducted based on official documents issued by the statistics agencies of Indonesia and Malaysia by comparing the trend of the area, production and productivity of people's oil palm plantations in the period 1998-2018, then the data processing was done by mathematical methods so that the performance of people's oil palm plantations from both countries could be known. Discussion is carried out from the results of data analysis with descriptive analytical methods. The results of this study are known that; The area of planting and harvesting people's oil palm plantations in Indonesia is higher than Malaysia and still allows it to continue to grow beyond the dominance of private plantations in Indonesia; CPO production of mustard coconut plantations.